2015
DOI: 10.4238/2015.november.30.15
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of backcross progeny of Passiflora L. (Passifloraceae) for pre-breeding genotype selection

Abstract: ABSTRACT. The Ward-MLM procedure was used to evaluate genetic variation in four backcross progenies and in their parents, hybrid F1 HD13 and donor parent Passiflora sublanceolata. Sixteen quantitative descriptors and five qualitative characteristics of relevance to ornamental flower production were assessed. Using the pseudo-F and pseudo-T² criteria, we identified four groups among these plants in two evaluation periods. In both evaluations, the BC 1 plants showed greater dissimilarity to their recurrent paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Agronomy, v. 45, e56482, 2023 In general, one backcross was effective in increasing agronomic performance of the BC 1 F 2 dwarf populations (Figure 1). Other satisfactory results derived from the first backcross were observed in passion fruit (Melo, Souza, Sousa, Viana, & Santos, 2015), eggplant (García-Fortea et al, 2019), and tomato (Finzi et al, 2020). Thus, as in a previous study performed by Gonçalves Neto et al (2010), performing two more backcrosses is suggested, as this will result in lines with commercial standard fruit and subsequent attainment of hybrids of the Santa Cruz type from dwarf lines, as obtained by Finzi et al (2017a).…”
Section: Resultsmentioning
confidence: 58%
“…Agronomy, v. 45, e56482, 2023 In general, one backcross was effective in increasing agronomic performance of the BC 1 F 2 dwarf populations (Figure 1). Other satisfactory results derived from the first backcross were observed in passion fruit (Melo, Souza, Sousa, Viana, & Santos, 2015), eggplant (García-Fortea et al, 2019), and tomato (Finzi et al, 2020). Thus, as in a previous study performed by Gonçalves Neto et al (2010), performing two more backcrosses is suggested, as this will result in lines with commercial standard fruit and subsequent attainment of hybrids of the Santa Cruz type from dwarf lines, as obtained by Finzi et al (2017a).…”
Section: Resultsmentioning
confidence: 58%
“…Beyond the analysis of variance (ANOVA) for quantitative floral descriptors, Ward-MLM multivariate analysis was also performed. The Ward-MLM multivariate procedure was performed using the distance matrix obtained by the logarithmic function of Gower coefficient (Gower, 1971), according to the method proposed by MELO et al (2015) on SAS Software analysis platform (SAS, 2000). The average values of the quantitative variables were included in the analysis together with the qualitative access data.…”
Section: Floral and Reproductive Genetic Diversity -Sowing Of The Different Melon Accessions Was Carried Out Inmentioning
confidence: 99%
“…The Ward-MLM multivariate strategy allowed to verify variability and quantify genetic diversity based on floral, reproductive and CMV resistance descriptors, including quantitative and qualitative descriptors. The selection and establishment of descriptors for the study of phenotypic variation and its inference on genetic diversity by the Ward-MLM strategy have been widely used in various crops and plant groups (CAMPOS et al, 2013;MELO et al, 2015;GONÇALVES et al, 2018). However, this is the first study that uses floral, reproductive and biotic stress resistance data in the joint multivariate analysis.…”
Section: Floral and Reproductive Genetic Diversity And Variability -mentioning
confidence: 99%
See 2 more Smart Citations